2005
DOI: 10.1111/j.1365-2966.2005.08800.x
|View full text |Cite
|
Sign up to set email alerts
|

XMMobservations of the high-redshift quasar RX J1028.6 - 0844 atz= 4.276: soft X-ray spectral flattening

Abstract: We present results from a new XMM–Newton observation of the high‐redshift quasar RX J1028.6 – 0844 at a redshift of 4.276. The soft X‐ray spectral flattening, as reported by a previous study with ASCA, is confirmed to be present, with, however, a reduced column density when modelled by absorption. The inferred column density for absorption intrinsic to the quasar is 2.1(+0.4−0.3) × 1022  cm−2 for cold matter, and higher for ionized gas. The spectral flattening shows remarkable similarity with that of two simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
5
22
1
Order By: Relevance
“…Due to the capability of the EPIC pn to observe down to low X-ray energies of 0.2 keV, Grupe et al (2004a) measured an intrinsic absorption column N H of at most a few times 10 22 cm À2 . From a 10 times longer XMM-Newton observation Yuan et al (2005) confirmed that, indeed, the source is not as highly absorbed as claimed from the ASCA data; the best-fit intrinsic cold absorption is N H ¼ 2:1 þ0:4 À0:3 ; 10 22 cm À2 . Yuan et al (2005) argue for an additional warm absorber with column density N H > 2 ; 10 22 cm À2 .…”
Section: Pmn J0525à3343supporting
confidence: 77%
See 1 more Smart Citation
“…Due to the capability of the EPIC pn to observe down to low X-ray energies of 0.2 keV, Grupe et al (2004a) measured an intrinsic absorption column N H of at most a few times 10 22 cm À2 . From a 10 times longer XMM-Newton observation Yuan et al (2005) confirmed that, indeed, the source is not as highly absorbed as claimed from the ASCA data; the best-fit intrinsic cold absorption is N H ¼ 2:1 þ0:4 À0:3 ; 10 22 cm À2 . Yuan et al (2005) argue for an additional warm absorber with column density N H > 2 ; 10 22 cm À2 .…”
Section: Pmn J0525à3343supporting
confidence: 77%
“…From a 10 times longer XMM-Newton observation Yuan et al (2005) confirmed that, indeed, the source is not as highly absorbed as claimed from the ASCA data; the best-fit intrinsic cold absorption is N H ¼ 2:1 þ0:4 À0:3 ; 10 22 cm À2 . Yuan et al (2005) argue for an additional warm absorber with column density N H > 2 ; 10 22 cm À2 .…”
Section: Pmn J0525à3343supporting
confidence: 77%
“…The lower limits shown with a (blue) pentagon and arrow in the 4–5 redshift bin corresponds to the existence of at least four blazars for which we have estimated a black hole mass larger than 10 9 M ⊙ . They are RXJ 1028.6−0844 ( z = 4.276; Yuan et al 2005); GB 1508+5714 ( z = 4.3; Hook et al 1995); PMN J0525−3343 ( z = 4.41; Worsley et al 2004a) and GB 1428+4217 ( z = 4.72; Worsley et al 2004b). There are other three blazars with 4 < z < 5 discussed in Yuan et al (2006), but they have X‐ray luminosities smaller than 10 47 erg s −1 .…”
Section: Discussionmentioning
confidence: 90%
“…The observed X-ray variability in both flux and spectrum reported here for Swift J1656.3-3302 is unusual, though not unprecedented in FSRQs. Indeed, a number of other high-z blazars show the same behavior, such as RX J1028.6−0844 (z = 4.2; Yuan et al 2005) and GB B1428+4217 (z = 4.7; Worsley et al 2006) and, in more recent studies, RBS 315 (z = 2.7; Tavecchio et al 2007) and QSO 0836+710 (z = 2.2; Sambruna et al 2007). This variability could be due to changes in the electron distribution at low energies, or may be a hint of the presence of an extra component, which becomes stronger or weaker as the source brightness changes.…”
Section: Discussionmentioning
confidence: 96%